ASSOCIATION OF CLINICAL DIAGNOSIS WITH HISTOPATHOLOGY IN VARIOUS SKIN DISEASES - Nageen, Safina; Waqas, Nadia; Mehmood, Asim (Journal of Ayub Medical College Abbottabad, 2021)
Background: Dermatological diagnosis are mainly clinical; however, skin biopsies are frequently done to support clinical diagnosis when in doubt. Aim of this study is to relate the clinical diagnosis of various dermatological conditions with histopathological diagnosis. Methods: In this descriptive prospective study, 223 patients were enrolled from dermatology OPD at Benazir Bhutto Hospital through non-probability consecutive sampling. Patients were diagnosed clinically and skin biopsies of all patients were taken after informed consent and clinical data was sent to a histopathologist. Results: Patients between ages of 2-85 years were evaluated. Mean age was 39.65±19.43 years. Out of total 223 patients 112 were males and 111 were females. Clinical diagnosis was same as histopathological diagnosis in 180 (80.7%). Out of 80.7% cases, most common disorder was Eczema, 18 cases (10%). The diseases lying in the inflammatory dermatosis group have highest sensitivity, specificity, PPV and NPV, i.e., 91.2%, 90.8%, 84.1% and 86.8% respectively. The discordance between clinical and histological diagnosis was highest in infectious disease group. The concordance between clinical and histological diagnosis in infectious diseases was just 28%. Conclusion: Documenting a histological diagnosis is essential in dermatology as most of the dermatosis have mimicking clinical presentation. The inflammatory lesions have superior clinical and histopathological correlation as compared to infectious diseases and therefore dermatologists should try to biopsy infective dermatosis more often rather than relying on clinical judgment solely.